Avaliação do cuidado na estratégia saúde da família em metrópoles do nordeste brasileiro - Rocha, Nadja de Sá Pinto Dantas (2013)
Objective: To evaluate the implementation of the Family Health Strategy (FHS) in Brazilian cities of the Northeast, expanding coverage, analyzing the progress, challenges and innovations. Methods: Multicentric Evaluation Research, Studies Baselines in urban centers, using as a case study method. Selected cases of Aracaju, being capital, advanced coverage with extended team, and Fortaleza, capital coverage incipient and minimal staff. In Fortaleza, purposive sample of 11 Units Primary (APS), 03 managers, 53 professionals and 109 users. In Aracaju, 09 units of APS, 02 managers, 36 professionals, and 90 users. Structured interviews for managers, and structured to professionals and users. Descriptive analysis focusing on the political and institutional dimensions, organization and comprehensive care. Results: There was consensus that the ESF is the preferred port users and acts as inducing changes in care. In the case of Fortaleza, the specificities were: care protocols and community activities aimed at chronic conditions (100%) , with greater participation of doctors and nurses (93%) ; conjunction with more complex services, but the teams reported difficulties with the examination center and experts, the long waits and poor access to local services were the main difficulties reported by users., As innovative practice, the therapeutic group of elderly caregivers mentioned by respondents; There was intersectoral initiatives and teams 87 % of users have participated in meetings about health problems. In the case of Aracaju, care protocols were directed to the lines of care and formulated locally, 85 % coverage of the population with FHS counterpart local financing; employees hired by public tender; 70 % of teams with expertise in public health center for continuing education acting; democratization in management; access technologies, welcoming and computerization in different integrated networks, and evaluation matrix. Conclusions: The ESF has promoted access to health care and inclusion of disadvantaged populations. Different perceptions and practices in the organization of care, with distinct trajectories of reorganization. In the case of Fortaleza, predominance of model programs valuing older, with evidence of advances in care practices and teamwork, but restricted to primary care practices and incipient in public policy perspective. In Aracaju, had network integration with technologies related to the family, in which the ESF is consolidated as public policy. It can be argued that the XII APS expanding coverage, exhibited efficacy, despite the challenges inherent to the different degrees of implementation